Implementasi Model TPSR melalui Permainan Tradisional untuk Meningkatkan Tanggung Jawab dan Motorik Kasar Siswa - Nurlita Sri Lestari; Dian Budiana; Yogi Akin (Jurnal Porkes, 2026)
This study aims to analyze the implementation of the Teaching Personal and Social Responsibility (TPSR) model through traditional games to improve elementary school students' responsibility and gross motor skills. Using a quantitative quasi-experimental approach with a Nonequivalent Control Group Design, this study involved 56 fourth-grade students at SDN Tenjolaya 3 Cicalengka. A sample of 40 students was selected via purposive sampling and divided into experimental (n = 20) and control (n = 20) groups. Data were collected using the Personal and Social Responsibility Questionnaire (PSRQ) and the Test of Gross Motor Development-2 (TGMD-2). The intervention consisted of eight sessions over six weeks, utilizing traditional games (engklek, lompat tali, gobak sodor, boy-boyan, and bola beracun). Data were analyzed using t-tests in SPSS. Results showed that the experimental group achieved significant increases in PSRQ (49.05 to 55.15; p = 0,000) and TGMD-2 scores (76.75 to 90.25; p = 0,000). Post-test independent t-tests confirmed significant differences between groups in responsibility (p = 0,001) and gross motor skills (p = 0,000). In conclusion, integrating the TPSR model and traditional games effectively and simultaneously improves students' affective and psychomotor domains in physical education.